Liquid phase based separation systems for depletion, prefractionation, and enrichment of proteins in biological fluids and matrices for in‐depth proteomics analysis—An update covering the period 2011–2014. Issue 1 (24th November 2014) - Puangpila, Chanida; Mayadunne, Erandi; El Rassi, Ziad; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> This review article expands on the previous one (S. Selvaraju and Z. El Rassi, Electrophoresis 2012, 33, 74–88) by reviewing pertinent literature in the period extending from early 2011 to present. As the previous review article, the present one is concerned with proteomic sample preparation (e.g., depletion of high‐abundance proteins, reduction of the protein dynamic concentration range, enrichment of a particular subproteome), and the subsequent chromatographic and/or electrophoretic prefractionation prior to peptide separation and identification by LC‐MS/MS. This review article, however, is distinguished from its earlier version by expanding on capturing/enriching subphosphoproteomes by immobilized metal affinity chromatography and metal oxide affinity chromatography. Seventy‐seven papers published in the period extending from mid‐2011 to the present have been reviewed. By no means this review article is exhaustive, given the fact that its aim is to give a concise treatment of the latest developments in the field.